Financial governance and the role of specialized intergovernmental organizations in Ukraine’s post-war reconstruction - Ivanova, Roksolana Yuriivna (Теоретичні питання юриспруденції і проблеми правозастосування: виклики ХХІ століття : тези доп. учасників X Міжнар. наук.-практ. конф. (Харків, 25 трав. 2025 р.), 2025)
While this research is focused on analyzing the financial governance systems and control mechanisms of specialized intergovernmental organizations (IGOs), their systems in turn focus on Ukraine’s post-war recovery. The effectiveness of international financial supervision and compliance enforcement is analyzed in the context of humanitarian crisis, economic disruption, and extensive reconstruction activities within the country. The assessment and evaluation center on the international organizations that control the distribution and utilization of expenditures on Ukraine and have an established working system of integrity and transparency. The methodology relies on institutional comparative analysis and legal framework review alongside policy evaluation of the international organizations’ control and regulatory mechanisms. Attention is drawn to the emerging relevance of specialized sector IGOs in the context of the increased complexity and disintegration of global financial governance. This work offers a profound assessment of the FSAP of the IMF, the AML/CFT supervision of the FATF, the Basel Committee’s supervision, and INTOSAI’s auditing standards. Key attention is directed towards the activities of the FAO, ILO, and ECOSOC NGOs in Ukraine regarding monitoring spending for agriculturally assisted social services, vocational education, and humanitarian aid. It has been established that these organizations operate within the bounds of treaty agreements and Memoranda of Understanding (MOU) and conduct audits, compliance reviews, and sanctions application under international legally accepted procedures.